Application of Gamma Irradiation to Ensure Safety and Preserve the Quality of Fresh Blueberries (Emerald) - Rodriguez Racca, Anabel; Mozgovoj, Marina Valeria; Bejarano, Melany; Godoy, Maria Fernanda; Cingolani, María Celeste; Lires, Carla Maria Laura; Pannunzio, Alejandro Adrián; Vaudagna, Sergio Ramon (Institute of Food Technologists (IFT), 2025)
This study aimed to evaluate the effect of gamma irradiation (0.6, 1.2, and 1.8 KGy doses) on rotavirus inactivation (RVA) and the quality of Esmerald fresh blueberries. Dosimetry measurements revealed absorbed doses of 0.72, 1.46, and 2.16 KGy. The D10 value for RVA inactivation was determined to be 3.03 ± 0.03 KGy, exceeding the maximum 2.5 KGy dose permitted for fresh fruit, indicating that gamma irradiation alone is insufficient for effective RVA inactivation without significantly impacting blueberry quality. On the other hand, the absorbed doses (0.72, 1.46, and 2.16 KGy) did not affect most of the physicochemical parameters or the nutritional profile. However, a dose-dependent decrease in mechanical properties and enzyme activity was observed. Therefore, achieving effective RVA inactivation in fresh blueberries could require a combined approach, integrating gamma irradiation, ideally at doses up to 1.46 KGy, with complementary methods. This combined strategy could offer a promising intervention for the inactivation of RVA in fresh produce.